Sistema de reciclaje de residuos textiles en procesos de tejeduría y confección para fabricar hilos como insumo en la generación copas corseteras (2023)
In this work we will find the basis and application of the circular economy directed towards textile companies, which seeks to use largely the waste generated also called scraps or remnants of these industries to re-integrate them into the economy thus prolonging its useful life, The objective is to give a second use to these wastes by means of the production of inputs for this type of companies, in this case the proposal was made for the production of bonding sheet cups with added value, which focuses on reducing the pollution generated, since it is well known that the textile industry is ranked as one of the most polluting industries in the world. Bogota in recent years has increased the number of textile companies to the point of matching Medellin which is clearly considered the leader in the production of textiles in Colombia, for this clear growth the textile companies of Bogota have been forced to bring inputs from other cities as well as from other countries since in Bogota are not able to find enough inputs to meet the demand. The idea originated from the above mentioned, with the objective of contributing positively to the environment as well as to generate new strategies to supply this type of needs in the textile industry, the enormous amount of waste generated in the weaving and clothing processes was identified, This type of virgin waste has not been given any use, therefore it was found by means of different classification processes applying the circular economy model. It is expected that through this proposal it will be possible to find the adequate model to produce yarns based on recycled fibers as an input to elaborate bonding sheets for corset cups, reusing textile waste generated in the weaving and clothing area.